Hypoglycemia awareness and its clinical implications in insulin-treated patients⁠ - Abdullah, Marwah Y.; Yatimi, Aldana M.; Aljamaan, Mohammed B.; Amoudi, Zaki T.; Alrefai, Nouf M.; Bamajboor, Afnan S.; Lashet, Zahra A.; Alsulami, Amani A.; Aljohani, Ammar S.; Alraddadi, Shahad H. (International Journal Of Community Medicine And Public Health, 2025)
Hypoglycemia is a significant complication of diabetes treatment. If left untreated, serious complications may occur. Mild hypoglycemia occurs in approximately 30% to 40% of those with insulin-treated type 2 diabetes. Overall prevalence of severe hypoglycemia in insulin-treated type 2 diabetes is 0.28 episodes per patient per year. Impaired awareness of hypoglycemia (IAH) is a possible complication of recurrent hypoglycemia episodes. Many prior studies have examined the prevalence of IAH in patients with type 1 diabetes, while there is limited data on the prevalence of IAH in insulin-treated type 2 diabetes. The following databases were used in systematic research: Medline (PubMed), Web of Science, and Scopus. Summaries of the found studies were exported by EndNoteX8, and duplicate studies were removed. Various mechanisms have been proposed in recent studies, such as the brain glucose transport hypothesis and the brain glycogen supercompensation hypothesis. It is important to assess the risk factors of IAH to avoid its significant complications. To successfully assess the risk factors, three methods of measuring are being used: Clarke, Gold, and Pedersen Bjergaard methods. The aim of this review is to discuss the prevalence, mechanisms, measurement, and clinical implications of IAH in insulin-treated type 2 diabetic patients.